Finite element method in computer simulation for improved patient care in dentistry: A systematic review - Denis Yu. Dyachenko; Svetlana V. Dyachenko (Кубанский научный медицинский вестник, 2021)
Background. The fi nite element method is gaining acknowledgment in Russia and other developed countries in a range of areas, including medicine. In stomatology, the method is applicable in research and implication of novel treatment and relevant material design.Objective. The review highlights usage of the fi nite element method in computer simulation to improve quality of patient dental care.Methods. The review analyses the state-of-the-art in current scientific literature. Records were mined in the PubMed and e-Library databases at a depth of 10 years, with selective inclusion of earlier articles. The query keywords were: finite element method [метод конечных элементов], computer simulation [компьютерная симуляция], quality of life improvement [повышение качества жизни], oral diseases [заболевания полости рта], dental treatment [стоматологическое лечение].Results. The review systematically surveys 56 scientific papers in the focus area for current state-of-the-art in the finite element analysis-empowered simulation in dentistry. The method’s rising employment is conditioned by its flexibility, 3D-object modelling simplicity and the rapid acquisition of reliable high-quality output. Its undoubted paramount advantage in dentistry is an explicit software visualisation of reliable results through co-modelling of multiple oral parameters.Conclusion. The growing acquaintance, mastering and use of this technique among researchers around the globe will give impetus to novel diagnosis and treatment, as well as relevant management algorithms in particular patient categories to enable personalisation of even mass dental check-up. This will reduce the number of visits, peri- and posttreatment error and complication rates for the improved patient’s quality of life and social rehabilitation.